The impact of timing and duration of thiopurine treatment on colectomy in ulcerative colitis: a national population‐based study of incident cases between 1989–2009. Issue 1 (10th November 2014) - Chhaya, V.; Saxena, S.; Cecil, E.; Chatu, S.; Subramanian, V.; Curcin, V.; Majeed, A.; Pollok, R. C.
Summary Background The role of thiopurines in altering the risk of colectomy in ulcerative colitis (UC) remains unclear. Aims To examine predictors of colectomy in UC and determine the impact of thiopurines on the risk of colectomy. Methods We constructed a population‐based cohort of incident cases of UC in the United Kingdom between 1989 and 2009. We determined trends in thiopurine usage and colectomy for three defined cohorts: era 1 (1989–1995), era 2 (1996–2002), era 3 (2003–2009). We used Cox regression to determine predictors of colectomy and quantified the impact of duration and timing of thiopurine use on the risk of colectomy. Results We identified 8673 incident cases of UC. 5‐year colectomy rates increased from 4.2%, 5.1% to 6.9% (P = 0.001) for era 1, era 2 and era 3, respectively, despite increasing thiopurine use. This was not significant after adjustment for predictors of colectomy (P = 0.06). There was a higher risk of colectomy in men (HR 1.44, 95% CI: 1.19–1.73), those diagnosed at an early age (HR 1.35, 95% CI: 1.04–1.75; 16–24 vs. 25–64) and early steroid users (HR 1.94, 95% CI: 1.59–2.37). 5‐ASA users were less likely to require a colectomy (HR 0.35, 95% CI: 0.28–0.44). Amongst thiopurine users, those treated for greater than 12 months had a 71% reduction in risk of colectomy (HR 0.29, 95% CI: 0.21–0.40). Early thiopurines offered no additional benefit. Conclusions Thiopurine exposure for greater than 12 months reduces the likelihood of colectomy by 71%. Young men and those requiring steroids within 3 months of diagnosis are at greatest risk of colectomy, and most likely to benefit from sustained thiopurine use.